Insect base-protein: A new opportunity in animal nutrition - Toviho, Odunayo; Bársony, Péter (Acta Agraria Debreceniensis, 2020)
The consumption of insect protein, as well as its use in animal feeding, has become a trend. This trend is particularly receiving a lot of attention in animal nutrition because the current protein source of the highest quality in animal feeding which is fishmeal is unsustainable, expensive and its demand is higher than supply. Insect protein can be of great potential in combating world hunger as the world population continues to increase. The potential of insect protein is wide-ranging, it could improve the economics of feed production, lead to cleaner production due to its low environmental footprint.This review focuses on the need, (nutritional and environmental) advantages of insect protein in feed production, as well as previous research findings.The unanimous conclusion of the reviewed papers is that insect protein has a great potential in feed production in terms of nutritional value, environmental implication, sustainability as well as economic implication.However, there is a need for the intensification of research on this alternative protein source in Europe, especially in aquaculture due to the approval of 7 insect species in aquafeeds by the European Union. Another reason for the intensification is that there is still much to be done as a result of past research which shows that growth effects vary based on species and inclusion level.